RETHINKING SECURITY POLICY OF BOSNIA AND HERZEGOVINA AND IMPROVING THE RESPONSE TO CHALLENGES AND THREATS (Security Dialogues, 2024)
The General framework agreement for peace in Bosnia and Herzegovina initialled in Dayton, USA, and signed in Paris, France, in 1995 stopped the war and brought peace. Bosnia and Herzegovina didn’t have a common army or police in that moment. First law enforcement agency on state level was State Bordes Service established in 2000 and after this several more has been established. Defense reform is completed in 2005 with the establishment of Armed Forces of Bosnia and Herzegovina. Security policy of Bosnia and Herzegovina have been adopted by the Presidency of Bosnia and Herzegovina on February 8th 2006. Since then no change has been made to this policy. Security sector in Bosnia and Herzegovina but also in other countries in the region of South Eastern Europe has been changed. Security threats and challenges significantly changed the perspective on security sector, organizational structure and response in many countries. Bosnia and Herzegovina don’t have National Security Strategy and Security policy is one the main documents for foreign policy, inner policy, defence policy, social policy, financial policy, democracy and human rights and protection of the environment.There is a clear need for redefinition of this document and approach to security challenges and threats in Bosnia and Herzegovina and harmonization with the documents of European union and neighboring countries in South eastern Europe.
Keywords: Security policy; Bosnia and Herzegovina